HEALTH CARE SPENDING AND ITS IMPACT ON LABOUR PRODUCTIVITY IN NIGERIA: 2000-2023 - Magbuin , Maryam; Akpan, Michael Simpson; Oniore, Jonathan Ojarikre (Economics and Statistics Research Journal (ESRJ), 2025)
Health is an important determinant of economic growth and will likely increase health care spending. Similarly, investments in health care can also increase labour productivity, thus an increase in economic growth and subsequent increase in the wellbeing of the population. As a result, understanding the determinants of healthcare spending and its impact on labour productivity is crucial for designing targeted interventions to improve health care access, quality, and equity in high-populated country like Nigeria. Thus, this paper examines the impact of health spending on labour productivity in Nigeria from 2000 to 2023 using time series data. The Autoregressive Distributed Lagged (ARDL) model was used as the main analytical technique. The short-run result revealed that health expenditure per capita, recurrent health expenditure, and out-of-pocket health spending have a negative influence on labour productivity, whereas capital health expenditure has positive influence on labour productivity. However, the long run result revealed that that health expenditure per capita is positively correlated with labour productivity. In other words, health expenditure per capita increases labour productivity. On the other hand, the findings indicated that recurrent health expenditure appears to affect labour productivity negatively over the long-run and an indication that bad managed recurrent health expenditure can negatively impact productivity. Similarly, the estimated impact of capital health expenditure on labour productivity is negative and insignificant eventually. This implies that capital health expenditure stimulates labour productivity negatively. The results indicate that out-of-pocket health spending affects labour productivity positively eventually. Therefore, this paper recommends that the Federal Ministry of Health intensify its investments in health care infrastructure in order to increase health expenditure per capita. Further, a thorough audit of recurrent health care spending by the Federal Ministry of Finance, which will likely enhance the efficiency and accountability of these expenditures, is recommended. In addition, the Federal Ministry of Health should actively promote the development of the health care industry and increase fixed asset investments in the health care sector